1995
DOI: 10.1159/000120927
|View full text |Cite
|
Sign up to set email alerts
|

Primary Diffuse Chiasmatic Germinomas: Differentiation from Optic Chiasm Gliomas

Abstract: Primary germ cell tumors confined to the optic nerves and chiasm without suprasellar extension are uncommon. These tumors appear similar to chiasmatic gliomas on both computed tomography and magnetic resonance imaging, potentially resulting in treatment errors if the diagnosis is based on radio-logic criteria alone. Unlike chiasmatic gliomas, suprasellar germinomas characteristically present with a clinical triad of endocrine abnormalities, diabetes insipidus, and visual complaints. We report the case of a 9-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Suprasellar germinomas are called neurohypophyseal germinomas because they grow in a line of the hypothalamic-pituitary stalk-neurohypophysis, i.e., the nerurohypophysis [1]. Optic nerve germinomas that oc-cur in the optic chiasm and the optic nerve are rarely reported [5][6][7][8][9][10][11][12] and differentiating between images of optic nerve germinoma and neurohypophyseal germinoma may be difficult when a tumor is large [8]. In other words, it may not be clear whether the site of the tumor origin is the optic chiasm and the optic nerve or the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suprasellar germinomas are called neurohypophyseal germinomas because they grow in a line of the hypothalamic-pituitary stalk-neurohypophysis, i.e., the nerurohypophysis [1]. Optic nerve germinomas that oc-cur in the optic chiasm and the optic nerve are rarely reported [5][6][7][8][9][10][11][12] and differentiating between images of optic nerve germinoma and neurohypophyseal germinoma may be difficult when a tumor is large [8]. In other words, it may not be clear whether the site of the tumor origin is the optic chiasm and the optic nerve or the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…No detailed cases of visual impairment preceding DI in suprasellar germinomas have been reported in the past. When a tumor is not limited to the optic nerve, as in optic nerve germinoma, visual impairment precedes DI [8]. This is because tumor cells infiltrate the optic nerve more so than the nerurohypophysis.…”
Section: Discussionmentioning
confidence: 99%
“…Tekkok et al [23] have reported a case of OCHG presenting as a huge intrasellar mass resembling a pituitary adenoma radiologically. Wilson et al [24] have described a case of suprasellar germinoma mimicking OCHG and have emphasized the requirement of histological confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review found reports of seven male patients only. [1][2][3][4][5][6] We present a young woman with a primary intrinsic optic chiasm germinoma. To our knowledge, this is the first report of a woman with this disease.…”
Section: Introductionmentioning
confidence: 99%